PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KREATIVITAS BELAJAR PADA MATA PELAJARAN ILMU GIZI SISWA TATA BOGA DI SMK - Sri Wahyu Andayani (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
The purpose of conducting this action research is to increase students' learning creativity in nutrition science competencies in culinary expertise in vocational schools through the application of discovery learning models. The research strategy is classroom action carried out in 2 (two) cycles including: planning, implementation, observation and reflection. The research subjects were 36 of tenth grade students of 2019/2020 academic year, while the object was students' creativity. The results showed that the creativity in learning nutrition increased. The improvement of students' learning creativity occured gradually. In pre-cycle, students were included in the category of not creative with a percentage of 53%. In the first cycle, the category changed into creative enough with a percentage of 42%. In the second cycle, students' creativity level also increased to a creative category with a percentage of 39%. Hence, it can be concluded that the discovery learning model can improve creativity in learning nutrition science.